A103 EARLY INITIATION OF ANTI-TNF THERAPY IS COST-SAVING COMPARED TO LATE INITIATION FOR PATIENTS WITH CROHN'S DISEASE. (1st March 2018) - Beilman, C L; Kirwin, E; Ma, C; McCabe, C; Fedorak, R; Halloran, B P
Abstract: Background: Anti-TNF therapies are effective for the induction and maintenance of remission in patients with Crohn's disease (CD), and are generally prescribed when patients fail to respond to conventional, less-costly medical therapies including steroids and immunomodulators. Our recent retrospective study showed that early initiation (within two years of diagnosis) of anti-TNF therapies reduced rates of surgery and loss of response requiring dose escalation. However, the cost effectiveness of this strategy is unknown, given the expensive nature of these medications. Aims: The aim of this study was to determine if early initiation of anti-TNF therapy is more cost-effective compared to delayed initiation for the management of CD. Methods: A Markov model was constructed to simulate the progression of patients with CD after the initiation of either infliximab or adalimumab. Using this model, we compared the lifetime cost-effectiveness of early (≤2 years after diagnosis) versus late (>2 years after diagnosis) initiation of anti-TNF therapy using published loss of response rates. Transition probabilities were determined through a literature search and costs were obtained from the Alberta Disease Registry. Utility scores were obtained from published literature using the Standard Gamble Approach. Deterministic and probabilistic sensitivity analysis was used to characterize uncertainty related to input parameters. Results: Over a patient's lifetime, early initiation of infliximab yielded an additional 1.02 quality-adjusted life years (QALYs) and saved $18, 054 compared to late initiation of infliximab. Early initiation of adalimumab yielded an additional 0.74 QALYs and saved $18, 526 compared to late initiation of adalimumab. At a willingness-to-pay threshold of $50, 000 per QALY, early initiation of both infliximab and adalimumab had a 68% chance of being cost-effective, while late initiation had a 32% chance of being cost-effective. Conclusions: Based on our current model, early initiation of either infliximab or adalimumab is cost-saving and dominates late initiation for patients with CD. These results may serve to support early treatment with anti-TNF therapy from both a cost and patient outcome perspective. Funding Agencies: CIHR